Model dynamic covalent organogels based on end‐linked three‐armed oligo(ethylene glycol) star macromonomers. Issue 20 (19th August 2021) - Apostolides, Demetris E.; Patrickios, Costas S.
Abstract: Dynamic covalent polymer networks represent a rapidly emerging class of polymeric materials, capable of self‐repairing when mechanically damaged. These materials also possess the ability to being dissolved and reformed, conferring upon objects made of such materials a longer service life, with positive economic and environmental impacts. While most such materials developed to date have a poorly‐defined structure, as they are randomly cross‐linked, better‐defined dynamic covalent polymer networks comprising model building blocks attract increasing interest, both because of enhanced mechanical properties and offering themselves for more precise studies. This investigation presents the development of model dynamic covalent polymer networks, cross‐linked via acylhydrazone bonds, and based on end‐linked star oligomers, that is, having a size intermediate between polymeric stars and monomers. After their appropriate end‐functionalization and purification, the oligomeric star building blocks were used to form polymeric networks in an organic solvent (organogels), which were subsequently characterized in terms of their swelling, mechanical, and dynamic properties. Abstract :